2019
DOI: 10.1371/journal.pone.0218751
|View full text |Cite
|
Sign up to set email alerts
|

Sedentism and plant cultivation in northeast China emerged during affluent conditions

Abstract: The reasons and processes that led hunter-gatherers to transition into a sedentary and agricultural way of life are a fundamental unresolved question of human history. Here we present results of excavations of two single-occupation early Neolithic sites (dated to 7.9 and 7.4 ka) and two high-resolution archaeological surveys in northeast China, which capture the earliest stages of sedentism and millet cultivation in the second oldest center of domestication in the Old World. The transition to sedentism coincid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
(29 reference statements)
0
27
0
Order By: Relevance
“…Recent study found a substantial population growth in Neolithic northern China started in the late seventh millennium BCE, which was likely initiated by the onset of millet-based agriculture 29 . Recent palaeoecological studies with high-resolution data also showed that, in North-central China, the transition to warm-wet climate took place at 8100-7900 BP, followed by a rapid development of sedentism and social complexity 33,34 . www.nature.com/scientificreports/ Figure S4 for the reconstructed phylogeny without an outgroup constraint.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study found a substantial population growth in Neolithic northern China started in the late seventh millennium BCE, which was likely initiated by the onset of millet-based agriculture 29 . Recent palaeoecological studies with high-resolution data also showed that, in North-central China, the transition to warm-wet climate took place at 8100-7900 BP, followed by a rapid development of sedentism and social complexity 33,34 . www.nature.com/scientificreports/ Figure S4 for the reconstructed phylogeny without an outgroup constraint.…”
Section: Discussionmentioning
confidence: 99%
“…These dates suggest that the trend towards sedentism was probably facilitated by ecological changes associated with the Holocene Climatic Optimum. Environmental conditions were arguably the primary driver of major contemporaneous shifts in settlement and subsistence patterns on the Mongolian Plateau, and probably across North-east Asia (Popov et al 2014;Janz 2016;Shelach-Lavi et al 2019). These ecological changes differed from region to region.…”
Section: Holocene Climatic Amelioration and The Onset Of Sedentismmentioning
confidence: 99%
“…This trajectory spans a period of roughly five thousand years, from c. 6000 BCE to c. 1200 BCE. Our project included systematic regional surveys [ 32 , 35 ] as well as test excavations at sites located during our survey [ 33 , 34 , 36 ]. All the data from the Fuxin regional project is openly available [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…and larger central sites (cities?). It started in the Xiaohexi period (c. 6000–5700 BCE), during which small scale sites with minimal investment in permanent structure may represent the incipient settling down of groups of complex hunter-gatherer societies [ 36 ]. During the ensuing Xinglongwa period (Xinglongwa c. 5700–5200 BCE) we see a rapid transition to relatively large-scale villages, which accompanies the development of agriculture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation